Influences of structural helicity of aortic dissection on endovascular repair - Shi-Cheng Jin; Zi-Long Zhao; Xuyang Zhang; Peng Lv; Cheng Yan; Tiantong Xu; Jialing Yang; Lixin Wang; Zhihui Dong; Daqiao Guo; Xi-Qiao Feng; Weiguo Fu; et al. (iScience, 2025)
Summary: Stanford type B aortic dissections often exhibit helical morphology. However, the influences of structural helicity on periprocedural and mid-to long-term adverse events after thoracic endovascular aortic repair (TEVAR) remain unclear. In this article, a total of 197 patients who underwent TEVAR between October 2019 and December 2020 were studied. Among them, 93 patients were excluded, and 104 patients were analyzed. The maximum helical angles and the maximum twists were measured using an efficient morphological method based on computed tomography angiography images. The whole dissecting aorta was divided into five zones. The visceral aortic zone exhibited the most pronounced structural helicity compared with other zones. Patients with the maximum helical angle larger or smaller than 200° were categorized into two groups, i.e., the groups of strong helicity and weak helicity. The patients in the strong helicity group exhibited a greater likelihood of experiencing adverse events after TEVAR.